Influence frequencies for technological and energy characteristics creamer - Ramsh, V. (Energy and Automation, 2015)
The influence of frequencies for angular velocity, technological and energy characteristics of milk separators. The dependences performance since static resistance milk separator and the specific power consumption of frequencies.